2006
DOI: 10.1128/jb.00573-06
|View full text |Cite
|
Sign up to set email alerts
|

Phototaxis and Impaired Motility in Adenylyl Cyclase and Cyclase Receptor Protein Mutants ofSynechocystissp. Strain PCC 6803

Abstract: We have carefully characterized and reexamined the motility and phototactic responses of Synechocystis sp. adenylyl cyclase (Cya1) and catabolite activator protein (SYCRP1) mutants to different light regimens, glucose, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, and cyclic AMP. We find that contrary to earlier reports, cya1 and sycrp1 mutants are motile and phototactic but are impaired in one particular phase of phototaxis in comparison with wild-type Synechocystis sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
(40 reference statements)
2
38
0
Order By: Relevance
“…These spectrum-specific photoresponses support the current view that the cAMPCrp complex is ecologically beneficial for optimal positioning of motile cells relative to incident light (Bhaya et al, 2006;Masuda & Ono, 2004). Indeed, it has been shown that intracellular cAMP is necessary and sufficient to restore phototactic motility used by cells to escape from the confines of a colony during suboptimal illumination (Bhaya et al, 2006;Terauchi & Ohmori, 1999).…”
supporting
confidence: 74%
“…These spectrum-specific photoresponses support the current view that the cAMPCrp complex is ecologically beneficial for optimal positioning of motile cells relative to incident light (Bhaya et al, 2006;Masuda & Ono, 2004). Indeed, it has been shown that intracellular cAMP is necessary and sufficient to restore phototactic motility used by cells to escape from the confines of a colony during suboptimal illumination (Bhaya et al, 2006;Terauchi & Ohmori, 1999).…”
supporting
confidence: 74%
“…Similarly, in this work, non-motile Dhfq mutant cells were also not rescued by cAMP addition (data not shown). However, there seems to be an important difference between Dsycrp1 and Dhfq mutant cells, that is to say motility of sycrp1 disruptants is affected only in the 'strong' phototaxis characterized by projections on the agar plate, while individual cells still appear motile (Bhaya et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…This surface-dependent phototaxis is mediated by Type IV pili (12)(13)(14). In addition, several components of the signal transduction pathway including photoreceptors have been identified using mutant screens and biochemical analyses (5,(15)(16)(17)(18)(19). It has been suggested that cells sense light direction rather than flux (7), but we have limited understanding of how this information is sensed and transduced to Type IV pili to cause directional motility.…”
Section: Introductionmentioning
confidence: 99%